The relationships between self‐transcendence and spiritual well‐being in cognitively intact nursing home patients. (11th February 2013) - Haugan, Gørill; Rannestad, Toril; Hammervold, Randi; Garåsen, Helge; Espnes, Geir A.
<x xml:space="preserve">Abstract</x> Background Self‐transcendence is considered a developmental process of personal maturity and a vital resource of well‐being in later adulthood. Measurement of the associations between self‐transcendence and spiritual well‐being in cognitively intact nursing home patients has not been previously published. Aims The aim of this study was to identify the relationships between self‐transcendence and spiritual well‐being in cognitively intact nursing home patients. Methods A cross‐sectional design using the self‐transcendence scale and the FACIT‐Sp spiritual well‐being questionnaire was adopted. A sample of 202 cognitively intact nursing home patients in mid‐Norway was selected to respond to the questionnaires in 2008 and 2009. Statistical analyses were conducted using lisrel 8.8 (Scientific Software International, Chicago, IL, USA) and structural equation modelling. Results A hypothesised structural equation model comprising a two‐factor construct of self‐transcendence and a three‐factor construct of spiritual well‐being demonstrated significant direct relationships between self‐transcendence and spiritual well‐being and total effects of self‐transcendence on spiritual well‐being. Implications for practice Facilitating patients' self‐transcendence, both interpersonally and intrapersonally, might increase spiritual well‐being among cognitively intact nursing home patients, which is seen to be of great importance to nursing home patients' overall satisfaction and satisfaction with staff. The two‐factor construct of self‐transcendence and the three‐factor construct of FACIT‐Sp allow a more complex examination of the associations between the constructs and prove more specific guidelines for nursing interventions promoting well‐being in nursing home patients.